2012
DOI: 10.1016/j.yfrne.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Importance of sex to pain and its amelioration; relevance of spinal estrogens and its membrane receptors

Abstract: Estrogens have a multitude of effects on opioid systems and are thought to play a key role in sexually dimorphic nociception and opioid antinociception. Heretofore, classical genomic actions of estrogens are largely thought to be responsible for the effects of these steroids on nociception and opioid antinociception. The recent discovery that estrogens can also activate estrogen receptors that are located in the plasma membrane, the effects of which are manifest in seconds to minutes instead of hours to days h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 203 publications
(261 reference statements)
2
41
0
Order By: Relevance
“…This mechanism may be particularly important for dynorphin-related nociceptive signaling in the spinal cord (Gintzler and Liu, 2012b). As previously described, dynorphin is an essential component of pregnancy-induced analgesia in rats.…”
Section: Estrogen Receptor Neurons and The Endogenous Opioid Systemmentioning
confidence: 57%
See 3 more Smart Citations
“…This mechanism may be particularly important for dynorphin-related nociceptive signaling in the spinal cord (Gintzler and Liu, 2012b). As previously described, dynorphin is an essential component of pregnancy-induced analgesia in rats.…”
Section: Estrogen Receptor Neurons and The Endogenous Opioid Systemmentioning
confidence: 57%
“…However, other studies, particularly those carried out by Alan Gintzler and collaborators have shown that under certain conditions, such as during pregnancy, dynorphin produces pain inhibition (for refs. see Gintzler and Liu, 2012a). Amandusson et al 1996.…”
Section: The Endogenous Opioid Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the many possible reasons for the disparity in pain responsiveness between men and women, which include cognitive and sociocultural differences, several studies have shown the importance of the sex hormone estrogen in regulating nociception (Craft, 2007;Fillingim et al, 2009;Gintzler and Liu, 2012).…”
Section: Introductionmentioning
confidence: 99%